GENOTYPIC RESPONSE IN CANOLA (BRASSICA SPECIES) AGAINST APHID (APHIDAE: HOMOPTERA) ATTACK - Sarwar, M.; Ahmad, N.; Siddiqui, Q. H.; Ali, A.; Tofique, M. (The Nucleus, 2020)
Present research work reports the results of work done, by determining the relative degree of responses of 12 canola genotypes (namely, Waster, CON I, CON II, CON III, Abasin-95, Dunkled, Rainbow, Shiralee, Hyola-42, Hyola-308, Hyola-401 and Oscar) against aphids’ infestation, under field conditions. In order to understand genotypic response, parameters with respect to incidence of aphids’ infestation and seeds yield obtained were recorded. Data pertaining to yield parameter as affected by different aphids infestation revealed that response of various genotypes were variable. The abundance of aphids was the least on Rainbow (44.92 aphids per plant), while, the most on CON. III (130.6 aphids per plant). Rainbow gave the better yield performance (3330.0 Kg/ha), while; the least yield (1720.0 Kg/ha) was obtained from genotype Hyola-401.